IMPACT OF COLLATERAL CIRCULATION ON BLOOD SUPPLY AND FUNCTION OF MYOCARDIUM - A. V. Fomichev; A. M. Chernyavsky; A. R. Tarkova; R. U. Ibragimov; Yu. E. Kareva; S. M. Minin; N. A. Nikitin (Российский кардиологический журнал)
Aim. To evaluate perfusion and functioning of myocardium in occluded coronary artery with various types of collateral blood flow.Material and methods. Ninety patients with three-vessel disease and obligate occlusion of the right coronary artery (RCA) according to the type of collateral flow development, were selected to 2 groups: first — 44 patients (49%) with I and II grades by Rentrop, second — 46 patients (51%) with grade III Rentrop collaterals. Perfusion scintigraphy data was analysed, with echocardiography and tissue Doppler.Results. Worsening of perfusion of myocardium inferior wall was found in patient of group 2 with non-significant defect of perfusion in 1st group patient. Stable perfusion defect in group 1 was 9,8±3,5%, in group 2 — 4,1±1,7%. While comparing tissue Doppler values, change in longitudinal deformation of inferior wall in the group with worse collaterals was -4,1±2,6, in group 2 -6,8±2,7. While assessing segmentary contractility of the inferior wall of the left ventricle, lower number of hypokinesis segments was found in group 2.Conclusion. Chronic occlusion of coronary artery with a weak collaterals is followed by worse parameters of local perfusion and function of myocardium. In a good condition of collaterals, regardless the non-significant perfusion disorders in myocardium at rest, there are prominent stress-defects and local contractility disorders of myocardium.